Developing the local model of monitoring organization for regional gas supply - Шевченко, Мария Валерьевна (Technology audit and production reserves, 2015)
The problem of monitoring the regional gas supply is urgent now, because of the obsolescence of equipment of gas supply systems and increasing the volume of leaks in gas pipelines. In these circumstances, it is necessary to improve the reliability of gas transport in regional systems of gas supply due to timely information on the results of monitoring, which takes place by the monitoring systems. One of the important tasks in the creation of a monitoring system is organization. The research allowed developing a conceptual model of the organization of monitoring, highlighting the main sub-steps of the monitoring organization of the regional gas supply. Partial mathematical models of the organization of a regional gas supply were developed based on the received information from the functional model. The calculations confirm the adequacy of the proposed partial models and allow making decisions under multicriteriality and fuzzy of initial data.